Research Exploration of Problem-Based Learning (PBL) Model and Metacognition Ability in Mathematics Learning: A Systematic Literature Review - Rachmi, Cut Nadia; Jupri, Al; Juandi, Dadang; Putri, Nadyati; Bulubaan, Santy (FKIP Universitas Lampung, 2025)
The Problem-Based Learning (PBL) model is one of the practical approaches to increase students' active participation, independent thinking skills, and awareness of the learning process, which will improve students' metacognition skills. Metacognition enables students to organize their learning strategies and improve learning outcomes. This research aims to identify, classify, and evaluate research results from primary studies that apply the PBL Model in measuring the improvement of students' metacognition skills in Indonesia using the systematic literature review (SLR) method. The protocol used in SLR refers to The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement, which includes the following four stages: (1) identification, (2) screening, (3) eligibility, (4) included. This systematic review leveraged covidence for comprehensive article screening and analysis, focusing on 30 carefully selected academic publications spanning from 2015 to 2024. This study examines the implementation of Problem-Based Learning (PBL) and its impact on students' mathematical metacognition skills. The analytical framework encompassed multifaceted research dimensions, including educational levels, geographical research contexts, publication timelines, mathematical domains, research methodologies, journal indexing criteria, and research outcomes. The analysis unveiled that publication frequency peaked in 2024, with a notable emphasis on secondary school-level investigations. The methodological analysis indicated a predominant preference for quantitative research approaches, particularly in studies examining spatial geometry concepts. The consolidated results provided substantial evidence that the implementation of the PBL model yielded positive and significant improvements in students' mathematical metacognition capabilities. Keywords: metacognition, problem-based learning model, systematic literature review.